2021
DOI: 10.3390/jof7100826
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Quorum-Quenching Lactonase Hydrolyzes Fungal Mycotoxin and Reduces Pathogenicity of Penicillium expansum—Suggesting a Mechanism of Bacterial Antagonism

Abstract: Penicillium expansum is a necrotrophic wound fungal pathogen that secrets virulence factors to kill host cells including cell wall degrading enzymes (CWDEs), proteases, and mycotoxins such as patulin. During the interaction between P. expansum and its fruit host, these virulence factors are strictly modulated by intrinsic regulators and extrinsic environmental factors. In recent years, there has been a rapid increase in research on the molecular mechanisms of pathogenicity in P. expansum; however, less is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…From this observation, we can speculate that AttM detoxifies AFB 1 mainly by disrupting the endolipid structure of AFB 1 . Dor et al demonstrated that bacterial AHL lactonases are also efficient in degrading mycotoxins . Pereyra, Martnez, and Cavaglieri showed that certain Bacillus species harbored the aii gene.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this observation, we can speculate that AttM detoxifies AFB 1 mainly by disrupting the endolipid structure of AFB 1 . Dor et al demonstrated that bacterial AHL lactonases are also efficient in degrading mycotoxins . Pereyra, Martnez, and Cavaglieri showed that certain Bacillus species harbored the aii gene.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Dor et al demonstrated that bacterial AHL lactonases are also efficient in degrading mycotoxins. 46 Pereyra, Martnez, and Cavaglieri showed that certain Bacillus species harbored the aii gene. This gene encodes an acyl homoserine lactone (Ahl) lactonase, which can degrade AFB 1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, this enzyme has weak antimicrobial activity, so it is advisable to combine it with an antibiotic; for example, with polymyxin B. Loaded in this combination to bacterial cellulose, which has the potential to be used as a dressing material with a good absorbency, thermolysin noticeably improves the effect of the antibiotic action. Lactonases (EC 3.1.1) produced by various microorganisms have potential antibacterial properties mostly against Gram-negative pathogenic bacteria and catalyze the hydrolysis of AHL and fungal mycotoxins [ 68 , 69 , 70 , 71 , 72 ]. However, their use is most often limited by the thermal instability or low activity of these enzymes despite the presence of some thermostable variants; for example, natural lactonase (AidB) from Bosea sp.…”
Section: Enzymes In Combinations With Other Enzymes Antibiotics Nanop...mentioning
confidence: 99%
“…This interest is due to a possible increase in the level of food safety for humans and animals arising from their consumption of food and feeds contaminated with mycotoxins, respectively, due to their detoxification under mild conditions as a result of the action of various enzymatic catalysts [ 74 , 75 , 76 ]. It is already known today that lactonases may be among such potentially effective destructors [ 76 , 77 , 78 ], since individual mycotoxins contain lactone structures similar to AHLs in their structures. Since His 6 -OPH is active in relation to AHLs and catalyzes their hydrolysis similarly to well-known lactonases, this determines the interest in the enzyme under discussion as a possible destructor of not only AHLs but also mycotoxins with corresponding chemical structures.…”
Section: Stabilized and Immobilized His-tagged Oph In The Hydrolysis ...mentioning
confidence: 99%